Penerapan BEPS Action Plan 4 sebagai Penangkal Penghindaran Pajak melalui Pembebanan Biaya Pinjaman - Ibrahim, Havidz; Sari, Dahlia (Politeknik Ganesha Medan, 2024)
Since 2015, the government has enacted an interest limitation rule to prevent excessive interest deduction and tax avoidance. However, this regulation is not aligned with the BEPS Action Plan 4 released by the OECD. Previous research had been conducted quantitatively to measure the effectiveness of the current interest limitation rule in Indonesia. However, the result still inconclusive. Some research concluded that the current interest limitation rule is effectively impacted the tax avoidance, while other research concluded otherwise. Furthermore, previous research suggested the importance of future research concerning the BEPS Action Plan 4 implementation in Indonesia. In order to fill the gap, this study aims to evaluate the effectiveness of the current regulation in Indonesia and provide ideal recommendations for implementing the BEPS Action Plan 4 to prevent tax avoidance. The research uses qualitative methods, including case studies and data acquisition techniques like interviews and document analysis. The study found that the current interest limitation rule in Indonesia is not effective in preventing tax avoidance. The OECD's BEPS Action Plan 4 recommendations are considered more effective as an anti-tax avoidance model. The ideal approach for implementation in Indonesia is the mandatory fixed ratio rule method based on EBITDA, with a de minimis threshold. The recommended ratio aligns with the OECD's recommendations, but should be periodically updated according to economic conditions. This approach should apply to both single entities and taxpayers who are group members.